MUTATION IN CONTINUOUS CULTURES III. : Mutational Responses in Escherichia coli - Kubitschek, H. E. (1964)
Kubitschek, H. E. (Argonne National Laboratory, Argonne, Ill.), and Lynn A. Gustafson. Mutation in continuous cultures. III. Mutational responses in Escherichia coli. J. Bacteriol. 88:1595–1597. 1964.—In continuous cultures of Escherichia coli K-12-W6 in minimal media, the growth rate dependence of the rate of mutation to resistance to bacteriophage T(5) depended upon the nutrient factor used to limit growth. In glucose-limited cultures, caffeine-induced mutation rates were predominantly proportional to generation rate. However, in cultures limited with the required amino acid, methionine, mutation rates appeared to be independent of generation rate, both for caffeineinduced and for spontaneous mutation. These mutational responses agree with those found earlier in tryptophan auxotrophs of E. coli B, suggesting that constancy of mutation occurs when growth is limited with a required amino acid. Since these two kinds of strains differ in their control of ribonucleic acid (RNA) synthesis, these results show that the RNA-control locus does not affect the mutational response.